Leaf Senescence in Wheat (Triticum aestivum L) Triggered by Drought Stress - Rustamova, Samira M.; Aliyeva, Durna R.; Isgandarova, Turana Y.; Huseynova, Irada M. (Agricultural Sciences: Techniques and Innovations Vol. 2, 2025)
Wheat is a globally important cereal crop whose productivity is often constrained by drought stress, which accelerates leaf senescence. This study investigated the biochemical and molecular mechanisms of natural and drought-induced senescence in wheat genotypes with contrasting drought tolerance. Plants were cultivated under controlled conditions, with drought stress imposed by terminating irrigation after the booting stage. Flag leaves were sampled at 7 (early grain filling), 14 (mid grain filling), 21 (late grain filling), 28 (milk ripeness), and 35 (dough ripeness) days after anthesis. Physiological parameters, including chlorophyll and total protein content, membrane stability index, malondialdehyde level, proline accumulation, and activities of antioxidant enzymes—superoxide dismutase, ascorbate peroxidase, guaiacol peroxidase, benzidine peroxidase, and catalase—were assessed. Additionally, expression profiles of SOD isoform genes (Cu/Zn-SOD, Fe-SOD, Mn-SOD) and WRKY transcription factors (WRKY14, WRKY36) were analyzed. Cu/Zn-SOD expression increased during senescence, peaking at the milk ripeness stage in naturally senescing plants and at the late grain filling stage in stress-treated plants, followed by a sharp decline. Fe-SOD expression remained high until late grain filling, then decreased sharply with advancing senescence, showing a consistent association with drought tolerance, as transcript levels were significantly higher in tolerant genotypes of both wheat species. Mn-SOD expression increased steadily throughout senescence in most variants, reaching its maximum at the dough ripeness stage. WRKY36 expression was upregulated in drought-tolerant genotypes under stress, while WRKY14 was more closely linked to senescence progression. Drought-tolerant genotypes also exhibited slower chlorophyll degradation, reduced lipid peroxidation, improved membrane stability, enhanced antioxidant activity, and higher proline accumulation. These findings provide valuable insights into the molecular and physiological responses of wheat to drought stress, highlighting key traits and gene expression patterns associated with stress tolerance and delayed senescence. This integrated understanding offers a solid foundation for the development of selection strategies and breeding programs aimed at enhancing wheat performance under water-limited conditions.